Polarizing film and image display device

CN117280256BActive Publication Date: 2026-10-30NITTO DENKO CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202280032363.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-06-30
Filing Date
2022-06-27
Publication Date
2026-10-30
Estimated Expiration
2042-06-27

AI Technical Summary

Benefits of technology

[0023]近年来,在高温高湿下使用的偏振膜用途有很多,如上所述,重要的是即使在高温高湿下也确保视觉辨认性。本发明的偏振膜尽管具备具有非偏振部的起偏镜,但即使在高温高湿下,视觉辨认性也优异。可得到这样的效果的理由可推定如下。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117280256B_ABST
    Figure CN117280256B_ABST
Patent Text Reader

Abstract

The present application relates to a polarizing film, which is laminated with a transparent protective film via an adhesive layer on at least one side of a polarizer designed so that a non-polarizing portion having a recess is formed on a single side, the hardness of the non-polarizing portion is H1 (GPa), the thickness of the thinnest portion is d1 (μm), the hardness of the portion of the adhesive layer which is in contact with the recess is H2 (GPa), the thickness of the thickest portion is d2 (μm), and H2 x (d2 / d1) ≥ 0.01.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a polarizing film having a transparent protective film laminated on at least one side of a polarizer, separated by an adhesive layer. This polarizing film can be used alone to form image display devices such as mobile phones, car navigation systems, computer monitors, and televisions, or it can be used as an optical film with the polarizing film laminated on it to form image display devices such as mobile phones, car navigation systems, computer monitors, and televisions. Background Technology

[0002] Image display devices such as mobile phones and laptop computers (PCs) incorporate internal electronic components such as sensors. In recent years, with the rapid proliferation of smartphones and touch-panel information processing devices, there is a demand for further improvements in sensor performance. Furthermore, to address the diversification of image display device shapes and the increasing functionality required, polarizing films with partial polarization properties are needed. To meet these requirements, polarizing mirrors with non-polarizing portions formed in a given area have been proposed; these non-polarizing portions are formed through chemical processing (e.g., Patent Documents 1 and 2).

[0003] Existing technical documents

[0004] Patent documents

[0005] Patent Document 1: Korean Patent Publication No. 10-2015-0086159

[0006] Patent Document 2: Japanese Patent Application Publication No. 2015-215609 Summary of the Invention

[0007] The problem the invention aims to solve

[0008] Generally speaking, the non-polarizing part of a polarizer is more prone to concavity in structure compared to the other parts (polarizing parts) of the polarizer. Therefore, when using a polarizer with a non-polarizing part to manufacture a polarizing film, air bubbles may sometimes remain near the concavity of the non-polarizing part.

[0009] In recent years, as a durability test required for polarizing films used in image display devices such as mobile phones and PCs, as well as automotive applications, there has been a humidification durability test, which involves exposure to high temperature and humidity, such as 85°C to 85% humidity, for a given time. When air bubbles remain near the recesses of the non-polarized portion of the polarizing film supplied for the aforementioned humidification durability test, existing polarizing films cannot prevent these bubbles, which were within product standards before the durability test, from expanding during the test. This raises concerns that the visual legibility of the polarizing film will significantly deteriorate after the durability test.

[0010] The present invention was developed in view of the above-mentioned actual situation, and its purpose is to provide a polarizing film and an image display device having a polarizing lens with a non-polarizing part, a polarizing film that can suppress bubble expansion in the polarizing film even under high temperature and high humidity, and excellent visual recognition.

[0011] Problem Solving Methods

[0012] The above-mentioned problem can be solved by the following configuration. That is, the present invention relates to a polarizing film (1), wherein a transparent protective film is laminated on at least one side of a polarizer with an adhesive layer in between, and the polarizer has a non-polarizing portion with a recess on one side. When the hardness of the non-polarizing portion is set to H1 (GPa), the thickness of the thinnest portion is set to d1 (μm), the hardness of the portion of the adhesive layer that is in contact with the recess is set to H2 (GPa), and the thickness of the thickest portion is set to d2 (μm),

[0013] H2×(d2 / d1)≥0.01.

[0014] Preferably, the polarizing film (2) is used when the stress relaxation rate of the portion of the adhesive layer that contacts the recess is set to O2 in the polarizing film (1).

[0015] O2 < 70%.

[0016] The preferred polarizing film (3) is one in which H1×d1>1.3 in the above polarizing film (1) or (2).

[0017] The preferred polarizing film (4) is, in any of the polarizing films (1) to (3) mentioned above, when the hardness of the transparent protective film stacked on the concave side of the polarizing mirror is set to H3 (GPa) and the thickness is set to d3 (μm),

[0018] H3×d3>4.

[0019] The preferred polarizing film (5) is one in which the maximum depth dh of the recess is 0.1 to 2.0 (μm) in any of the polarizing films (1) to (4).

[0020] The preferred polarizing film (6) is one in which the adhesive layer between the portion of the polarizing mirror other than the non-polarizing portion and the transparent protective film is 2 μm or less.

[0021] In addition, the present invention relates to an image display device having any of the polarizing films (1) to (6) described above, wherein the non-polarizing portion of the polarizing film is disposed at a position corresponding to the sensor portion.

[0022] The effects of the invention

[0023] In recent years, polarizing films used in high temperature and high humidity environments have had many applications. As mentioned above, it is important to ensure visual legibility even under these conditions. Although the polarizing film of this invention has a polarizer with a non-polarizing portion, it exhibits excellent visual legibility even under high temperature and high humidity conditions. The reasons for this effect can be presumed as follows.

[0024] When image display devices such as mobile phones and PCs are placed under high temperature and high humidity for extended periods, or in automotive applications, the polarizing portion of the polarizing lens in the polarizing film shrinks, while the non-polarizing portion tends to elongate. As a result, if air bubbles remain near the recesses of the non-polarizing portion, these bubbles expand as the non-polarizing portion elongates. Since the bubbles and the non-polarizing portion have a refractive index difference, the expansion of bubbles near the non-polarizing portion of the polarizing film tends to degrade visual discernibility in the non-polarizing portion. The polarizing film of the present invention is designed such that: when the hardness of the non-polarizing portion of the polarizing lens is set to H1 (GPa), the thickness of the thinnest part of the non-polarizing portion of the polarizing lens is set to d1 (μm), the hardness of the portion of the non-polarizing portion of the polarizing lens in the adhesive layer that bonds the polarizing lens to the transparent protective film where it contacts the recess is set to H2 (GPa), and the thickness of the thickest part of the portion of the non-polarizing portion of the polarizing lens in the adhesive layer where it contacts the recess is set to d2 (μm), H2×(d2 / d1)≥0.01. As a result, even if air bubbles remain near the concave part of the non-polarized portion of the polarized film, the expansion of the air bubbles under high temperature and high humidity can be suppressed, which can make the visual recognition of the polarized film excellent.

[0025] In this invention, the aforementioned effect is achieved because the relationship H2×(d2 / d1)≥0.01 is satisfied. When d1 is relatively thin compared to d2, that is, when (d2 / d1) is large, the thickness of the adhesive layer can be sufficiently ensured. Therefore, even when the polarizing film is placed under high temperature and high humidity, heat-induced deformation of the polarizing and non-polarizing portions of the polarizer can be suppressed, thus suppressing the expansion of bubbles. Therefore, even when H2 is relatively small, the above relationship is satisfied. As a result, the visual recognizability of the polarizing film is excellent even under high temperature and high humidity.

[0026] On the other hand, when d1 is relatively thicker than d2, that is, when (d2 / d1) is small, the thickness of the adhesive layer used to suppress bubble expansion is insufficient. Therefore, when the hardness of the adhesive layer is increased to suppress bubble expansion, that is, when H2 is relatively large, the above relationship is satisfied. As a result, the visual recognition of the polarizing film is excellent even under high temperature and high humidity conditions.

[0027] It should be noted that, based on in-depth research conducted by the inventors, the following insights were obtained for the first time in this invention: since the expansion of bubbles can be suppressed even under high temperature and high humidity conditions when d1, d2 and H2 satisfy the above-mentioned relationship, the polarization film has excellent visual recognition. Attached Figure Description

[0028] Figure 1 This is an example of a cross-sectional schematic diagram of a polarizing film according to one embodiment of the present invention.

[0029] Figure 2 This is a schematic diagram of a polarizing film sample with an adhesive layer, for which the expansion rate of bubbles was measured. Detailed Implementation

[0030] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. It should be noted that the thickness ratios in the drawings are merely examples and are not intended to limit the scope of the invention.

[0031] Figure 1 The diagram shown is a cross-sectional schematic of a polarizing film according to one embodiment of the present invention. In this embodiment, a transparent protective film 3 is laminated on one side of the polarizing lens 1, separated by an adhesive layer 2. It should be noted that, in the present invention, transparent protective films may also be laminated on both sides of the polarizing lens, separated by adhesive layers.

[0032] The polarizer 1 has a polarizing portion 1A with a recess 1h formed on one side. The method for forming the non-polarizing portion of the polarizer will be described later. It should be noted that... Figure 1 The illustrated embodiment shows an example where the recess 1h is present only on the upper side of the drawing and not on the lower side. However, depending on the method and conditions for forming the non-polarizing portion, there may be cases where the polarizing mirror surface opposite to the recess 1h has some recess. In such cases, in this invention, the portion with a large recess depth (usually the recess on the side that has been processed for forming the non-polarizing portion in the polarizing mirror) is designated as the recess 1h.

[0033] Figure 1The polarizing film 10 shown is designed such that: the hardness of the non-polarizing portion 1A of the polarizer 1 is set to H1 (GPa), the thickness of the thinnest part of the non-polarizing portion 1A of the polarizer 1 is set to d1 (μm), the hardness of the portion of the non-polarizing portion 1A of the polarizer 1 that contacts the recess 1h in the adhesive layer 2 that bonds the polarizer 1 to the transparent protective film 3 is set to H2 (GPa), and the thickness of the thickest part of the portion of the non-polarizing portion 1A of the polarizer 1 that contacts the recess 1h in the adhesive layer 2 is set to d2 (μm), then H2×(d2 / d1)≥0.01. As a result, even if air bubbles remain near the recess 1h of the non-polarizing portion 1A of the polarizing film 10, the thickness and / or hardness of the adhesive layer can be sufficiently ensured, suppressing heat-induced deformation of the polarizing and non-polarizing portions of the polarizer. Therefore, the expansion of air bubbles under high temperature and high humidity can be suppressed, resulting in excellent visual recognizability of the polarizing film 10. From the viewpoint of improving the visual recognizability of the polarizing film, H2×(d2 / d1)≥0.03 is preferred, and H2×(d2 / d1)≥0.07 is more preferred. Furthermore, it is required that the polarizing film does not curl (good curlability), but if the aforementioned "H2×(d2 / d1)" is too high, the curlability will deteriorate. Therefore, 0.35≥H2×(d2 / d1) is preferred, and 0.23≥H2×(d2 / d1) is more preferred. "The portion of the adhesive layer 2 in which the polarizing lens 1 and the transparent protective film 3 are bonded together, where the non-polarizing portion 1A of the polarizing lens 1 is in contact with the recess 1h" refers to the entire portion of the adhesive layer 2 that overlaps with the recess 1h when viewed from above. It should be noted that the methods for measuring the hardness H1, H2, and thicknesses d1 and d2 will be described later.

[0034] exist Figure 1 In the polarizing film 10 shown, if the stress relaxation rate of the portion of the non-polarizing portion 1A of the polarizing lens 1 that contacts the recess 1h in the adhesive layer 2 that bonds the polarizing lens 1 to the transparent protective film 3 is set to O2, and O2 < 70%, then even if air bubbles remain near the recess 1h of the non-polarizing portion 1A of the polarizing film 10, the expansion of the air bubbles under high temperature and high humidity can be more effectively suppressed, which is therefore preferable. Furthermore, O2 < 65% is more preferable, and even more preferably 10% < O2. It should be noted that the method for measuring the stress relaxation rate O2 will be described later.

[0035] In addition, Figure 1 In the polarizing film 10 shown, when the thickness and / or hardness of the non-polarizing portion 1A is sufficiently ensured, specifically when H1×d1 > 1.3, deformation of the non-polarizing portion 1A is easily suppressed. Therefore, even if air bubbles remain near the recess 1h of the non-polarizing portion 1A of the polarizing film 10, the expansion of the air bubbles under high temperature and high humidity can be more effectively suppressed, which is preferable. Furthermore, 1.35 > H1×d1 is preferred.

[0036] In addition, Figure 1 In the polarizing film 10 shown, when the hardness of the transparent protective film 3, which is stacked on the recess 1h side of the non-polarizing portion 1A of the polarizer 1, is set to H3 (GPa) and the thickness is set to d3 (μm), and H3×d3>4 is satisfied, the transparent protective film becomes less prone to deformation. As a result, the portion of the adhesive layer 2 where the non-polarizing portion 1A of the polarizer 1 is in contact with the recess 1h becomes less prone to deformation. Therefore, even if air bubbles remain near the recess 1h of the non-polarizing portion 1A of the polarizing film 10, the expansion of air bubbles under high temperature and high humidity can be suppressed more effectively, which is preferable. From the viewpoint of further suppressing the expansion of air bubbles under high temperature and high humidity, H3×d3>7 is preferred, H3×d3>10 is more preferred, H3×d3>13 is even more preferred, and 22>H3×d3 is preferred. It should be noted that the methods for measuring the hardness H3 and the thickness d3 will be described later.

[0037] exist Figure 1 In the polarizing film 10 shown, when the maximum depth dh of the recess 1h in the non-polarizing portion 1A of the polarizing mirror 1 is 0.1 to 2.0 (μm), it is particularly preferable that even if air bubbles remain near the recess 1h in the non-polarizing portion 1A of the polarizing film 10, the expansion of air bubbles under high temperature and high humidity can be more effectively suppressed. It should be noted that the method for measuring the depth dh will be described later.

[0038] It should be noted that a thicker adhesive layer bonding the polarizer and the transparent protective film together is better at suppressing bubble expansion under high temperature and humidity, and is therefore preferred. However, if the adhesive layer is too thick, there is a tendency for the damp heat durability of the polarizing film to deteriorate. Figure 1 In the polarizing film 10 shown, when the thickness of the adhesive layer between the portion of the polarizing mirror 1 other than the polarizing portion 1A (hereinafter also referred to as the "polarizing portion") and the transparent protective film 3 is 2 μm or less, the damp heat durability of the polarizing film can be maintained and the expansion of bubbles under high temperature and high humidity can be suppressed, which is therefore preferred.

[0039] Figure 1 The polarizing film 10 shown illustrates a case where a transparent protective film 3 is stacked on one side of the polarizer 1, separated by an adhesive layer 2. However, in the polarizing film of the present invention, for example, a transparent protective film, a phase retardation film, or a phase retardation layer, the same or different, may be further provided on the side of the polarizer 1 opposite to the side where the transparent protective film 3 is stacked, separated by an adhesive layer. The transparent protective film, the phase retardation film, and the phase retardation layer will be described later.

[0040] The components constituting the polarizing film of the present invention will be described below.

[0041] [Polarizing filter]

[0042] The polarizing film includes a polarizing lens composed of a resin film containing a dichroic substance, and a non-polarizing portion is formed within the polarizing lens. Typically, the non-polarizing portion is a region where the content of the dichroic substance is lower than that of the portion of the polarizing lens other than the non-polarizing portion (low-concentration region). However, the non-polarizing portion in this invention can be a layer after the dichroic material has been extracted from the polarizing lens, or it can be another layer that does not contain the dichroic material, but it is not limited to these. With this configuration, compared to forming through-holes using mechanical methods (e.g., by using a carving knife, a plotter, water spraying, etc. to mechanically remove them), quality problems such as cracks, delamination (interlayer peeling), and paste overflow can be avoided.

[0043] Examples of methods for introducing a non-polarized portion into a polarizer include methods that extract and decolorize a dichroic substance from the polarizer through chemical treatment to form a non-polarized portion (hereinafter also referred to as the "chemical treatment method"), and methods that form a non-polarized portion by decomposing the dichroic substance using a laser or the like (hereinafter also referred to as the "laser method"). Among these methods, the chemical treatment method can adjust the content of the dichroic substance itself in the non-polarized portion to a lower level, and compared with the laser method, it can better maintain the transparency of the non-polarized portion, and is therefore preferred.

[0044] In a polarizing film, the number, arrangement, shape, and size of the non-polarizing portions can be appropriately designed. For example, it can be designed according to the position, shape, and size of the sensor portion of the image display device on which it is mounted. Specifically, it can be designed such that the non-polarizing portions do not correspond to any part of the image display device other than the sensor (e.g., the image display portion).

[0045] The transmittance of the non-polarized portion (e.g., transmittance measured at 23°C using light with a wavelength of 550 nm) is preferably 50% or more, more preferably 60% or more, further preferably 75% or more, and particularly preferably 90% or more. Such transmittance ensures the desired transparency. For example, when the non-polarized portion is aligned with the sensor section of the image display device, adverse effects on the sensor's imaging performance can be prevented.

[0046] The polarizer preferably exhibits absorption dichroism in the wavelength range of 380 nm to 780 nm. The single-cell transmittance (Ts) of the polarizing portion of the polarizer (the portion of the polarizer other than the non-polarizing portion) is preferably 39% or more, more preferably 39.5% or more, further preferably 40% or more, and particularly preferably 40.5% or more. It should be noted that the theoretical upper limit for single-cell transmittance is 50%, and the practical upper limit is 46%. Furthermore, the single-cell transmittance (Ts) is a Y value obtained by measuring with a 2-degree field of view (C light source) using JIS Z8701 and after visibility correction; for example, it can be measured using a UV-Vis spectrophotometer (manufactured by Nippon Spectrophotometer Co., Ltd., product name: V7100). The degree of polarization of the polarizing portion of the polarizer is preferably 99.8% or more, more preferably 99.9% or more, and further preferably 99.95% or more.

[0047] The thickness of the polarizer (resin film) can be set to any suitable value. The thickness of the polarizer is typically 0.5 μm to 80 μm. Preferably, the thickness is 30 μm or less, more preferably 25 μm or less, further preferably 18 μm or less, particularly preferably 12 μm or less, and even more particularly preferably less than 8 μm. The thickness is preferably 1 μm or more. The thinner the resin film used as the polarizer, the shorter the time it takes to reduce the content of dichroic substances during the process of contacting the alkaline solution described later.

[0048] Examples of dichroic substances include iodine and organic dyes, which can be used alone or in combination of two or more, with iodine being preferred. This is because it can readily form a non-polarized portion through contact with the alkaline solution described later.

[0049] The content of the dichroic material in the non-polarized portion is preferably 1.0% by mass or less, more preferably 0.5% by mass or less, and even more preferably 0.2% by mass or less. If the content of the dichroic material in the non-polarized portion is within this range, the desired transparency can be sufficiently imparted to the non-polarized portion. Therefore, for example, when the non-polarized portion corresponds to the sensor section of the image display device, excellent imaging performance can be achieved from both the viewpoints of brightness and hue. On the other hand, the lower limit of the content of the dichroic material in the non-polarized portion is generally below the detection limit value. It should be noted that when iodine is used as the dichroic material, the iodine content can be determined, for example, from the X-ray intensity measured by fluorescence X-ray analysis and a calibration curve prepared in advance using a standard sample.

[0050] The difference between the content of dichroic material in other parts and the content of dichroic material in the non-polarized part is preferably 0.5% by mass or more, and more preferably 1% by mass or more.

[0051] As the resin for forming the above-mentioned resin film, any suitable resin can be used, but polyvinyl alcohol resins (hereinafter referred to as "PVA resins") are preferred. Examples of PVA resins include polyvinyl alcohol and ethylene-vinyl alcohol copolymers. Polyvinyl alcohol is obtained by saponifying polyvinyl acetate. Ethylene-vinyl alcohol copolymers are obtained by saponifying ethylene-vinyl acetate copolymers. The degree of saponification of PVA resins is generally 85 mol% or more and less than 100 mol%, preferably 95.0 mol% to 99.95 mol%, and more preferably 99.0 mol% to 99.93 mol%. The degree of saponification can be determined according to JISK6726-1994. By using PVA resins with such a degree of saponification, polarizers with excellent durability can be obtained. If the saponification is too high, there is a concern about gelation.

[0052] The average degree of polymerization of PVA resins can be appropriately selected according to the purpose. The average degree of polymerization is usually 1,000 to 10,000, preferably 1,200 to 4,500, and more preferably 1,500 to 4,300. It should be noted that the average degree of polymerization can be determined according to JIS K 6726-1994.

[0053] A polarizer with a non-polarizing section can be manufactured by a chemical treatment method that involves contacting a treatment solution, such as an alkaline solution, with a resin film containing a dichroic substance. When iodine is used as the dichroic substance, the iodine content at the contact point can be easily reduced (decolorized) by contacting the desired area of ​​the resin film with the alkaline solution. Specifically, through contact, the alkaline solution can penetrate into the interior of the resin film. The iodine complex contained in the resin film is reduced to iodide ions by the alkali contained in the alkaline solution. By reducing the iodine complex to iodide ions, the transmittance of the contact point can be increased. Furthermore, the iodine that has become iodide ions moves from the resin film into the solvent of the alkaline solution. The non-polarizing section thus obtained can maintain its transparency well. Specifically, when the transmittance is increased by destroying the iodine complex, the iodine remaining in the resin film will re-form an iodine complex with the use of the polarizer, and the transmittance will decrease. However, this problem can be prevented by reducing the iodine content.

[0054] As a method of contacting the resin membrane with an alkaline solution, any suitable method can be used, such as dripping, coating, or spraying the alkaline solution onto the resin membrane; or immersing the resin membrane in the alkaline solution.

[0055] When exposed to alkaline solutions, the resin film can be protected with any suitable protective material to prevent the alkaline solution from contacting areas other than the desired location (and to prevent a decrease in the content of dichroic substances). Specifically, protective films and surface protective films can be examples of protective materials for the resin film. Protective films can be used directly as protective films for polarizers. Surface protective films are used temporarily during the manufacture of the polarizer and are removed from the resin film at any appropriate time; therefore, they are typically bonded to the resin film through an adhesive layer. Other specific examples of protective materials include photoresists.

[0056] Any suitable basic compound can be used as the aforementioned basic compound. Examples of basic compounds include: hydroxides of alkali metals such as sodium hydroxide, potassium hydroxide, and lithium hydroxide; hydroxides of alkaline earth metals such as calcium hydroxide; inorganic alkali metal salts such as sodium carbonate; organic alkali metal salts such as sodium acetate; and ammonia. Among these, hydroxides of alkali metals and / or alkaline earth metals are preferred, and sodium hydroxide, potassium hydroxide, and lithium hydroxide are even more preferred. This is because they can ionize dichroic substances with good efficiency, thereby making it easier to form the non-polarized portion. These basic compounds can be used alone or in combination of two or more.

[0057] As a solvent for alkaline solutions, any suitable solvent can be used, specifically including: water, ethanol, methanol and other alcohols, diethyl ether, benzene, chloroform, and mixtures thereof. Among these, water and alcohols are preferred from the perspective of the good mobility of ionized dichroic substances to the solvent.

[0058] The concentration of the alkaline solution is, for example, 0.01N to 5N, preferably 0.05N to 3N, and more preferably 0.1N to 2.5N. When the concentration is within this range, the desired non-polarized portion can be formed well.

[0059] The temperature of the alkaline solution is, for example, 20°C to 50°C. The contact time of the alkaline solution is set, for example, according to the thickness of the resin film, the type and concentration of the alkaline compound contained in the alkaline solution. The contact time is, for example, 5 seconds to 30 minutes, preferably 5 seconds to 5 minutes.

[0060] In one embodiment, upon contact with an alkaline solution, the surface of the resin film is covered by a surface protective film with at least a portion exposed. For example, this can be achieved by attaching a surface protective film with small circular through-holes to a polarizer (resin film) and bringing the alkaline solution into contact with it. In this case, it is preferable that the other side of the resin film (the side without the surface protective film) is also protected.

[0061] It should be noted that the aforementioned resin film can be elongated. When the resin film is elongated, it is preferable that the resin film and the protective material are laminated in a roll-to-roll manner. Here, "roll-to-roll" means that the rolls of film are transported while aligning their length directions during lamination. For example, through-holes are formed in the elongated surface protective film at given intervals along its length and / or width directions. Methods for manufacturing polarizers using the aforementioned elongated resin film, and surface protective films for manufacturing elongated resin films, are described in Japanese Patent Application Publications Nos. 2016-027135, 2016-027136, 2016-027137, 2016-027138, and 2016-027139, and these descriptions are incorporated herein by reference.

[0062] When contacting an alkaline solution, it is preferable to prepare the resin film in a state suitable for use as a polarizing mirror. Specifically, various treatments are preferably performed, such as swelling treatment, stretching treatment, dyeing treatment using the aforementioned dichroic substance, crosslinking treatment, cleaning treatment, and drying treatment. It should be noted that during these various treatments, the resin film can be a resin layer formed on a substrate. The laminate of the substrate and the resin layer can be obtained, for example, by coating a coating solution containing the resin film-forming material onto the substrate, or by laminating the resin film onto the substrate.

[0063] The above-described dyeing process is typically performed by adsorbing a dichroic substance. Examples of such adsorption methods include: impregnating a resin membrane in a dyeing solution containing the dichroic substance, coating the dyeing solution onto the resin membrane, and spraying the dyeing solution onto the resin membrane. The method of impregnating the resin membrane in the dyeing solution is preferred because the dichroic substance can be adsorbed well.

[0064] When using iodine as the dichroic substance, an aqueous iodine solution is preferred as the staining solution. The amount of iodine added is preferably 0.04 to 5.0 parts by mass relative to 100 parts by mass of water. To improve the solubility of iodine in water, an iodide is preferably added to the aqueous iodine solution. Potassium iodide is preferred as the iodide. The amount of iodide added is preferably 0.3 to 15 parts by mass relative to 100 parts by mass of water.

[0065] In the above stretching process, the resin film is typically stretched unidirectionally to 3 to 7 times its original strength. It should be noted that the stretching direction can correspond to the absorption axis direction of the resulting polarizer.

[0066] In the case where the non-polarized portion of the polarizer is formed by decolorization using chemical treatment, the contact surface of the alkaline solution (non-polarized portion) is concave compared to other polarized portions, thereby forming a recess in the non-polarized portion. The maximum depth of the recess varies depending on the thickness of the polarizer and the contact conditions with the alkaline solution (temperature / time, etc.), but it is preferred when it is 0.1 to 2.0 (μm), especially 0.1 to 1.0 (μm), as it is easy to improve the visual recognizability of the polarizing film under high temperature and high humidity conditions.

[0067] In the case where the non-polarizing part of the polarizer is formed by decolorization based on chemical treatment, the thickness and hardness of the non-polarizing part can be changed by appropriately adjusting the manufacturing conditions of the non-polarizing part (e.g., "the time (seconds) of immersing the polarizing film in a 1 mol / L (1N) sodium hydroxide aqueous solution", "the time (seconds) of immersing the polarizing film in a 1 mol / L (1N) hydrochloric acid", "the drying temperature (°C) after NaOH treatment and HCl treatment").

[0068] In this invention, the manufacturing of the polarizing mirror can be further included with any appropriate steps as needed. Examples include steps to reduce alkali metals and / or alkaline earth metals, and steps to remove the alkaline solution. These steps can be performed at any appropriate stage of the manufacturing method described above.

[0069] By contacting an alkaline solution with a resin film, hydroxides of alkali metals and / or alkaline earth metals can remain at the contact area. Furthermore, by contacting the alkaline solution with the resin film, metal salts of alkali metals and / or alkaline earth metals can be generated at the contact area. These metal salts generate hydroxide ions, which react (decompose / reduce) with dichroic substances (e.g., iodine complexes) present around the contact area, thus expanding the unpolarized region (low concentration region). Therefore, by reducing the amount of alkali metals and / or alkaline earth metals, the expansion of the unpolarized region over time can be suppressed, thereby maintaining the desired shape of the unpolarized region. Details of the process for reducing alkali metals and / or alkaline earth metals are described, for example, in Japanese Patent Application Publications Nos. 2015-215609, 2015-215610, and 2015-215611, which are incorporated herein by reference.

[0070] Specific examples of methods for removing the aforementioned alkaline solutions and / or post-crosslinking solutions include cleaning, wiping with a cloth, suction removal, natural drying, heating drying, air drying, and vacuum drying. Cleaning solutions used for cleaning include, for example, water (pure water), methanol, ethanol, and mixtures thereof; water is preferred. The number of cleaning cycles is not particularly limited and can be performed multiple times. In the case of removal by drying, the drying temperature is, for example, 20°C to 100°C.

[0071] [Transparent Protective Film]

[0072] The polarizing film of the present invention has a transparent protective film laminated on at least one side of the polarizer, separated by an adhesive layer. Furthermore, in the polarizing film of the present invention, for example, the same or different transparent protective films may be further provided on the side of the polarizer opposite to the side where the transparent protective film is laminated, separated by an adhesive layer.

[0073] As materials constituting the transparent protective film, thermoplastic resins with excellent transparency, mechanical strength, thermal stability, moisture barrier properties, and isotropy can be used, for example. Specific examples of such thermoplastic resins include cellulose resins such as cellulose triacetate, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, cyclic polyolefin resins (norbornene resins), polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. The transparent protective film may contain one or more suitable additives. Examples of additives include: ultraviolet absorbers, antioxidants, lubricants, plasticizers, mold release agents, anti-coloring agents, flame retardants, nucleating agents, antistatic agents, pigments, colorants, etc. The content of the aforementioned thermoplastic resin in the transparent protective film is preferably 50-100% by mass, more preferably 50-99% by mass, further preferably 60-98% by mass, and particularly preferably 70-97% by mass. When the content of the aforementioned thermoplastic resin in the transparent protective film is less than 50% by mass, there are concerns that the high transparency inherent in the thermoplastic resin may not be fully expressed.

[0074] Furthermore, as the material for forming the transparent protective film, materials with excellent transparency, mechanical strength, thermal stability, moisture barrier properties, and isotropy are preferred, especially those with a moisture permeability of 150 g / m². 2 / less than 24h, especially preferred is 140g / m 2 / less than 24h, further preferably 120g / m 2 / less than 24 hours.

[0075] Functional layers such as a hard coating, anti-reflective layer, anti-adhesion layer, diffusion layer, or anti-glare layer can be applied to the side of the transparent protective film that is not bonded to the polarizer. It should be noted that the aforementioned functional layers such as the hard coating, anti-reflective layer, anti-adhesion layer, diffusion layer, and anti-glare layer can be used not only to protect the transparent protective film itself, but also to be separately applied as layers different from the transparent protective film.

[0076] The thickness of the transparent protective film can be appropriately determined. Generally speaking, considering factors such as strength, processability, operability, and thinness, it is about 1 to 500 μm, preferably 1 to 300 μm, more preferably 5 to 200 μm, further preferably 10 to 200 μm, and even more preferably 20 to 80 μm.

[0077] As the aforementioned transparent protective film, a phase retardation film having a frontal phase difference of 40 nm or more and / or a thickness direction phase difference of 80 nm or more can be used. Typically, the frontal phase difference is controlled within the range of 40 to 200 nm, and the thickness direction phase difference is typically controlled within the range of 80 to 300 nm. When the phase retardation film is used as the transparent protective film, it also functions as a transparent protective film, thus enabling thinner designs. In the polarizing film of the present invention, for example, a phase retardation film may be further provided on the side of the polarizer opposite to the side where the transparent protective film is stacked, separated by an adhesive layer.

[0078] Examples of phase retardation films include: birefringent films formed by unidirectional or bidirectional stretching of polymer raw materials, alignment films of liquid crystal polymers, and phase retardation films formed by using a film to support an alignment layer of liquid crystal polymers. The thickness of phase retardation films is not particularly limited, generally ranging from 20 to 150 μm.

[0079] As a phase retardation film, an inverse wavelength dispersion type phase retardation film that satisfies the following equations (1) to (3) can be used:

[0080] 0.70<Re

[450] / Re

[550] <0.97···(1)

[0081] 1.5×10 -3 <Δn<6×10 -3 ···(2)

[0082] 1.13 < NZ < 1.50 ···(3)

[0083] (In the formula, Re

[450] and Re

[550] are the in-plane phase difference values ​​of the phase difference film measured at 23℃ using light with wavelengths of 450nm and 550nm, respectively. Δn is nx-ny, i.e., in-plane birefringence, when the refractive indices of the slow axis and fast axis of the phase difference film are set to nx and ny, respectively. NZ is the ratio of nx-nz to nx-ny when nz is set as the refractive index of the thickness direction of the phase difference film, where nx-nz is the thickness direction birefringence and nx-ny is the in-plane birefringence).

[0084] A phase retardation layer can be provided in the polarizing film of the present invention. The phase retardation layer can be a single layer or a single layer, and it can also serve as a protective layer for the polarizer. In the polarizing film of the present invention, for example, a phase retardation layer can be provided on the side of the polarizer opposite to the side where the transparent protective film is stacked, separated by an adhesive layer. The type, quantity, combination, arrangement position, and characteristics of the phase retardation layer can be appropriately set according to the purpose.

[0085] The phase retardation layer is preferably formed using a liquid crystal compound. A solvent containing the liquid crystal compound can be applied using, for example, a wire rod, a gap coater, a comma coater, a gravure coater, or a slit die. The applied liquid crystal solution can then be allowed to dry naturally or by heating. It should be noted that the liquid crystal solution is preferably applied at a concentration lower than the isotropic phase-liquid crystal phase transition concentration, i.e., in an isotropic phase state. In this case, it can be stably oriented by methods such as rubbing or photo-orientation.

[0086] [Adhesive layer]

[0087] The polarizing film of the present invention has a transparent protective film laminated on at least one side of the polarizer via an adhesive layer. The adhesive layer may, for example, be formed by a cured layer of a curable resin composition.

[0088] The present invention is characterized by the following design: when the hardness of the non-polarizing portion formed on the polarizer is set to H1 (GPa), the thickness of the thinnest portion is set to d1 (μm), the hardness of the portion of the adhesive layer that contacts the recess is set to H2 (GPa), and the thickness of the thickest portion is set to d2 (μm), H2×(d2 / d1)≥0.01 is satisfied. The material constituting the adhesive layer in such a manner as satisfying H2×(d2 / d1)≥0.01 can be solely the curable resin composition described later, or a combination of an easy-to-bond composition and a curable resin composition can be used.

[0089] In the polarizing film 10 of the present invention, the thickness of the adhesive layer between the polarizing portion of the polarizing lens 1 and the transparent protective film 3 is preferably 2 μm or less, and more preferably 1.8 μm or less. It should be noted that, as a lower limit for the thickness of this adhesive layer, in order to ensure adhesion, it is preferably 0.5 μm.

[0090] Curable resin compositions can be classified into free radical polymerization curable resin compositions and cationic polymerization curable resin compositions. In this invention, active energy rays with wavelengths ranging from 10 nm to less than 380 nm are referred to as ultraviolet light, and active energy rays with wavelengths ranging from 380 nm to 800 nm are referred to as visible light.

[0091] Examples of monomeric components constituting free radical polymerizable resin compositions include compounds having carbon-carbon double bonds such as (meth)acryloyl or vinyl groups. These monomeric components can be monofunctional free radical polymerizable compounds or polyfunctional free radical polymerizable compounds having two or more polymerizable functional groups. Furthermore, one of these free radical polymerizable compounds can be used alone, or two or more can be used in combination. As such free radical polymerizable compounds, compounds having (meth)acryloyl groups are preferred, for example. It should be noted that in this invention, (meth)acryloyl refers to acryloyl and / or methacryloyl, and "(meth)" has the same meaning below.

[0092] Examples of monofunctional free radical polymerizable compounds include (meth)acrylamide derivatives having a (meth)acrylamide group. (meth)acrylamide derivatives are preferred in terms of ensuring adhesion to polarizers and various transparent protective films, as well as in terms of fast polymerization speed and excellent productivity. Specific examples of (meth)acrylamide derivatives include: N-methyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-butyl (meth)acrylamide, N-hexyl (meth)acrylamide, and other N-alkyl (meth)acrylamide derivatives; N-hydroxymethyl (meth)acrylamide, N-hydroxyethyl (meth)acrylamide, N-hydroxymethyl-N-propyl (meth)acrylamide, and other N-hydroxyalkyl (meth)acrylamide derivatives; aminomethyl (meth)acrylamide, aminoethyl (meth)acrylamide, and other N-aminoalkyl (meth)acrylamide derivatives; N-methoxymethylacrylamide, N-ethoxymethylacrylamide, and other N-alkoxy (meth)acrylamide derivatives; mercaptomethyl (meth)acrylamide, mercaptoethyl (meth)acrylamide, and other N-mercaptoalkyl (meth)acrylamide derivatives; and so on. In addition, the nitrogen atom, which is a (meth)acrylamide group, forms heterocyclic (meth)acrylamide derivatives, such as N-acryloylmorpholine, N-acryloylpiperidine, N-methacryloylpiperidine, and N-acryloylpyrrolidine.

[0093] Among the aforementioned (meth)acrylamide derivatives, N-hydroxyalkyl (meth)acrylamide derivatives are preferred from the perspective of adhesion to polarizing mirrors and various transparent protective films. In addition, as monofunctional free radical polymerizable compounds, various (meth)acrylic acid derivatives having (meth)acryloyloxy groups can be cited as examples. Specific examples include: methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, 2-methyl-2-nitropropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, n-pentyl methacrylate, tert-pentyl methacrylate, 3-pentyl methacrylate, 2,2-dimethylbutyl methacrylate, n-hexyl methacrylate, hexadecyl methacrylate, n-octyl methacrylate, 2-ethylhexyl methacrylate, 4-methyl-2-propylpentyl methacrylate, n-octadecyl methacrylate, and other alkyl methacrylates (1-20 carbon atoms).

[0094] In addition, examples of the aforementioned (meth)acrylic acid derivatives include: cyclohexyl (meth)acrylate, cyclopentyl (meth)acrylate, and other cycloalkyl (meth)acrylates; benzyl (meth)acrylate and other aralkyl (meth)acrylates; 2-isoborneol (meth)acrylate, 2-norborneol methyl (meth)acrylate, 2-norborneol methyl (meth)acrylate, 5-norbornen-2-yl methyl (meth)acrylate, 3-methyl-2-norborneol methyl (meth)acrylate, and (meth)acrylic acid... Polycyclic (meth)acrylates such as dicyclopentenyl ester, dicyclopentenoxyethyl ester, and dicyclopentyl ester; (meth)acrylates containing alkoxy or phenoxy groups such as 2-methoxyethyl ester, 2-ethoxyethyl ester, 2-methoxymethoxyethyl ester, 3-methoxybutyl ester, ethyl carbitol ester, phenoxyethyl ester, and alkylphenoxy polyethylene glycol ester; etc.

[0095] In addition, examples of the above-mentioned (meth)acrylic acid derivatives include: 2-hydroxyethyl (meth)acrylic acid, 2-hydroxypropyl (meth)acrylic acid, 3-hydroxypropyl (meth)acrylic acid, 2-hydroxybutyl (meth)acrylic acid, 4-hydroxybutyl (meth)acrylic acid, 6-hydroxyhexyl (meth)acrylic acid, 8-hydroxyoctyl (meth)acrylic acid, 10-hydroxydecyl (meth)acrylic acid, 12-hydroxylaurate (meth)acrylic acid, etc.; hydroxyalkyl (meth)acrylic acid esters such as [4-(hydroxymethyl)cyclohexyl]methyl acrylate, cyclohexanediol mono(meth)acrylic acid, and 2-hydroxy-3-phenoxypropyl (meth)acrylic acid; glycidyl (meth)acrylic acid, 4-hydroxybutyl (meth)acrylic acid glycidyl ether, etc., containing epoxy groups; 2,2,2-trifluoroethyl (meth)acrylic acid, etc. Halogenated (meth)acrylates such as 2,2,2-trifluoroethyl ethyl ester, tetrafluoropropyl (meth)acrylate, hexafluoropropyl (meth)acrylate, octafluoropentyl (meth)acrylate, heptadecafluorodecyl (meth)acrylate, and 3-chloro-2-hydroxypropyl (meth)acrylate; alkylaminoalkyl (meth)acrylates such as dimethylaminoethyl (meth)acrylate; oxy-heterocyclic butyl (meth)acrylates such as 3-oxetane butyl methyl (meth)acrylate, 3-methyloxetane butyl methyl (meth)acrylate, 3-ethyloxetane butyl methyl (meth)acrylate, 3-butyloxetane butyl methyl (meth)acrylate, and 3-hexyloxetane butyl methyl (meth)acrylate; heterocyclic (meth)acrylates such as tetrahydrofurfuryl (meth)acrylate and butyrolactone (meth)acrylate; neopentyl glycol (meth)acrylate adducts of hydroxypentanoic acid; and p-phenylphenol (meth)acrylate.

[0096] In addition, examples of monofunctional free radical polymerizable compounds include: (meth)acrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, and other carboxyl-containing monomers.

[0097] In addition, examples of monofunctional free radical polymerizable compounds include: N-vinylpyrrolidone, N-vinyl-ε-caprolactam, methylvinylpyrrolidone, and other lactam vinyl monomers; vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazolium, and vinylpyrrole. Vinyl monomers containing nitrogen-containing heterocycles, such as azoles and vinylmorpholine.

[0098] Furthermore, as a monofunctional radical polymerizable compound, a radical polymerizable compound having an active methylene group can be used. A radical polymerizable compound having an active methylene group is a compound having an active double bond group such as a (meth)acryloyl group at the end or in the molecule, and having an active methylene group. Examples of active methylene groups include acetoacetyl, alkoxymalonyl, or cyanoacetyl. The preferred active methylene group is acetoacetyl. Specific examples of free radical polymerizable compounds containing an active methylene group include: 2-acetylacetoxyethyl methacrylate, 2-acetylacetoxyethyl propyl methacrylate, 2-acetylacetoxyethyl-1-methylethyl methacrylate, and other acetylacetoxyethyl alkyl methacrylates; 2-ethoxymalonyl ethyl methacrylate, 2-cyanoacetoxyethyl methacrylate, N-(2-cyanoacetoxyethyl)acrylamide, N-(2-propionylacetoxybutyl)acrylamide, N-(4-acetylacetoxyethylmethylbenzyl)acrylamide, and N-(2-acetylacetylaminoethyl)acrylamide. The preferred free radical polymerizable compound containing an active methylene group is an acetylacetoxyethyl alkyl methacrylate.

[0099] In addition, examples of multifunctional free radical polymerizable compounds having two or more polymerizable functional groups include: tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol diacrylate, 2-ethyl-2-butylpropanediol di(meth)acrylate, bisphenol A di(meth)acrylate, bisphenol A ethylene oxide adduct di(meth)acrylate, bisphenol A propylene oxide adduct di(meth)acrylate, bisphenol A diglycidyl ether di(meth)acrylate, neopentyl glycol di(meth)acrylate, tricyclodecanediethanol di(meth)acrylate, cyclic trimethylolpropane formal(meth)acrylate, and dimethylolpropane formal(meth)acrylate. Esterifications of methacrylic acid and polyols, such as alkyldiol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and EO-modified diglycerol tetra(meth)acrylate, as well as 9,9-bis[4-(2-(meth)acryloyloxyethoxy)phenyl]fluorene. Specific examples include ARONIX M-220 (manufactured by Toa Synthetic Co., Ltd.), LIGHT ACRYLATE 1,9ND-A (manufactured by Kyoeisha Chemical Co., Ltd.), LIGHT ACRYLATE DGE-4A (manufactured by Kyoeisha Chemical Co., Ltd.), LIGHT ACRYLATE DCP-A (manufactured by Kyoeisha Chemical Co., Ltd.), SR-531 (manufactured by Sartomer Co., Ltd.), and CD-536 (manufactured by Sartomer Co., Ltd.). In addition, as needed, examples include: various epoxy (meth)acrylates, urethane (meth)acrylates, polyester (meth)acrylates, and various (meth)acrylate monomers.

[0100] In this invention, the curable resin composition may contain, in addition to free radical polymerizable compounds, acrylic oligomers formed by polymerizing (meth)acrylic acid monomers. By including acrylic oligomers in the adhesive composition, curing shrinkage during irradiation with active energy rays and subsequent curing can be reduced, thereby decreasing interfacial stress between the adhesive layer and adhered materials such as polarizers and optical films. As a result, the reduction in adhesion between the adhesive layer and the adhered materials can be suppressed.

[0101] Considering workability and uniformity during application, a low viscosity curing resin composition is preferred; therefore, acrylic oligomers polymerized from (meth)acrylic acid monomers are also preferably low viscosity. As a low-viscosity acrylic oligomer capable of preventing curing shrinkage of the adhesive layer, its weight-average molecular weight (Mw) is preferably 15,000 or less, more preferably 10,000 or less, and particularly preferably 5,000 or less. On the other hand, to sufficiently suppress curing shrinkage of the cured layer (adhesive layer), the weight-average molecular weight (Mw) of the acrylic oligomer is preferably 500 or more, more preferably 1,000 or more, and particularly preferably 1,500 or more.Examples of (meth)acrylate monomers constituting acrylic oligomers include: methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, 2-methyl-2-nitropropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, n-pentyl methacrylate, tert-pentyl methacrylate, 3-pentyl methacrylate, 2,2-dimethylbutyl methacrylate, n-hexyl methacrylate, etc. Cetyl methacrylate, n-octyl methacrylate, 2-ethylhexyl methacrylate, 4-methyl-2-propylpentyl methacrylate, n-octadecyl methacrylate, and other alkyl methacrylates (1-20 carbon atoms), as well as cycloalkyl methacrylates (e.g., cyclohexyl methacrylate, cyclopentyl methacrylate, etc.), aralkyl methacrylates (e.g., benzyl methacrylate, etc.), polycyclic methacrylates (e.g., 2-isobornyl methacrylate, 2-norbornyl methacrylate, etc.). Borneol methyl ester, 5-norbornen-2-yl methyl methacrylate, 3-methyl-2-norbornol methyl methacrylate, etc.; hydroxyl-containing (meth)acrylates (e.g., hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 2,3-dihydroxypropyl methyl butyl methacrylate, etc.); alkoxy or phenoxy (meth)acrylates (2-methoxyethyl methacrylate, 2-ethoxyethyl methacrylate, 2-methoxymethoxyethyl methacrylate, 3-methoxybutyl methacrylate). Ethyl carbitol acrylate (meth)acrylate, phenoxyethyl acrylate (meth)acrylate, etc.), epoxy-containing meth)acrylates (e.g., glycidyl acrylate (meth)acrylate, etc.), halogen-containing meth)acrylates (e.g., 2,2,2-trifluoroethyl meth)acrylate, 2,2,2-trifluoroethyl meth)acrylate, tetrafluoropropyl meth)acrylate, hexafluoropropyl meth)acrylate, octafluoropentyl meth)acrylate, heptadecafluorodecyl meth)acrylate, etc.), alkylaminoalkyl meth)acrylates (e.g., dimethylaminoethyl meth)acrylate, etc.). These meth)acrylates can be used alone or in combination of two or more. Specific examples of acrylic oligomers (E) include "ARUFON" manufactured by Toa Synthetic Co., Ltd., "ACTFLOW" manufactured by Soken Chemical Co., Ltd., and "JONCRYL" manufactured by BASF Japan Ltd.

[0102] The amount of acrylic oligomers in the composition is typically preferred to be 15 parts by mass or less, relative to the total amount of monomer components in the curable resin composition (100 parts by mass). Excessive content of acrylic oligomers in the composition can lead to a sharp decrease in the reaction rate when the composition is irradiated with active energy rays, resulting in poor curing. On the other hand, to sufficiently suppress the curing shrinkage of the adhesive layer, it is preferable to contain 3 parts by mass or more of acrylic oligomers in the composition.

[0103] The curable resin composition preferably contains a photopolymerization initiator. The photopolymerization initiator can be appropriately selected based on the active energy of the radiation. In the case of curing by ultraviolet or visible light, a photopolymerization initiator that is pyrolyzed by ultraviolet or visible light is used. Examples of such photopolymerization initiators include: benzoyl, benzophenone, benzoylbenzoic acid, 3,3′-dimethyl-4-methoxybenzophenone, and other benzophenone compounds; aromatic ketone compounds such as 4-(2-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)one, α-hydroxy-α,α′-dimethylacetophenone, 2-methyl-2-hydroxyphenylacetone, α-hydroxycyclohexylphenyl ketone, etc.; acetophenone compounds such as methoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxyacetophenone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one, etc.; and benzoin methyl ether. Benzoin ethers, such as benzoin ethyl ether, benzoin isopropyl ether, benzoin butyl ether, and anisolein methyl ether; aromatic ketals, such as benzoin dimethyl ketal; aromatic sulfonyl chlorides, such as 2-naphthalenesulfonyl chloride; photoactive oximes, such as 1-phenyl-1,1-propanedione-2-(O-ethoxycarbonyl)oxime; thioxanthones, such as 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-dichlorothioxanthone, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone; camphorquinone; haloketones; acylphosphine oxides; and acylphosphonates.

[0104] The amount of the photopolymerization initiator is 20 parts by mass or less relative to the total amount of polymerizable compound A (100 parts by mass). The amount of the photopolymerization initiator is preferably 0.01 to 20 parts by mass, more preferably 0.05 to 10 parts by mass, and even more preferably 0.1 to 5 parts by mass.

[0105] Furthermore, when using a visible light-curable resin composition, it is particularly preferable to use a photopolymerization initiator that is highly sensitive to light above 380 nm. The use of photopolymerization initiators that are highly sensitive to light above 380 nm will be described later.

[0106] As the above-mentioned photopolymerization initiator, it is preferred to use the compound shown in general formula (1) alone; or to use the compound shown in general formula (1) in combination with the photopolymerization initiator with high sensitivity to light above 380 nm described later.

[0107] [Chemical Formula 1]

[0108]

[0109] (where R is in the formula) 1 and R 2 Represents -H, -CH2CH3, -iPr, or Cl, R 1 and R 2 (These may be the same or different). When using the compound shown in general formula (1), the adhesion is superior compared to using a photopolymerization initiator with high sensitivity to light above 380 nm alone. Among the compounds shown in general formula (1), R is particularly preferred. 1 and R 2 The compound is a diethylthioxanthone with the formula -CH2CH3. The composition ratio of the compound of general formula (1) in the curable resin composition is preferably 0.1 to 5% by mass, more preferably 0.5 to 4% by mass, and even more preferably 0.9 to 3% by mass, relative to the total amount of the curable resin composition.

[0110] Furthermore, it is preferable to add a polymerization initiator as needed. Examples of polymerization initiators include triethylamine, diethylamine, N-methyldiethanolamine, ethanolamine, 4-dimethylaminobenzoic acid, methyl 4-dimethylaminobenzoate, ethyl 4-dimethylaminobenzoate, and isoamyl 4-dimethylaminobenzoate, with ethyl 4-dimethylaminobenzoate being particularly preferred. When using a polymerization initiator, its addition amount is typically 0-5% by mass, preferably 0-4% by mass, and most preferably 0-3% by mass, relative to the total amount of the curable resin composition.

[0111] In addition, known photopolymerization initiators can be used in combination as needed. Since transparent protective films with UV absorption capabilities do not transmit light below 380 nm, photopolymerization initiators that are highly sensitive to light above 380 nm are preferred. Examples include: 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholino)phenyl]-1-butanone, 2,4,6-trimethylbenzoyl diphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and bis(η5-2,4-cyclopentadien-1-yl)bis(2,6-difluoro-3-(1H-pyrrole-1-yl)phenyl)titanium, etc.

[0112] The curable resin composition preferably contains a silane coupling agent. Specific examples of silane coupling agents include vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-epoxypropoxypropyltrimethoxysilane, 3-epoxypropoxypropylmethyldiethoxysilane, 3-epoxypropoxypropyltriethoxysilane, p-styryltrimethoxysilane, 3-methacryloyloxypropylmethyldimethoxysilane, 3-methacryloyloxypropylmethyldiethoxysilane, 3-methacryloyloxypropyltriethoxysilane, 3-methacryloyloxypropyltriethoxysilane, and so on, which are compounds that can be cured by active energy rays.

[0113] Preferably, it is 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-epoxypropoxypropyltrimethoxysilane, 3-epoxypropoxypropylmethyldiethoxysilane, or 3-epoxypropoxypropyltriethoxysilane.

[0114] The amount of silane coupling agent incorporated relative to the total amount of the adhesive composition is preferably in the range of 0.01 to 20% by mass, more preferably 0.05 to 15% by mass, and even more preferably 0.1 to 10% by mass. This is because when the amount incorporated exceeds 20% by mass, the storage stability of the adhesive composition deteriorates, and when it is less than 0.1% by mass, the adhesive water resistance effect cannot be fully exerted.

[0115] Specific examples of inactive energy-curable silane coupling agents other than those mentioned above include: 3-ureopropyltriethoxysilane, 3-chloropropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, bis(triethoxysilylpropyl)tetrasulfide, 3-isocyanate-propyltriethoxysilane, imidazole silane, etc.

[0116] As needed, the curable resin composition may be further formulated with compounds of the following general formula (3) into the adhesive composition.

[0117] [Chemical Formula 2]

[0118]

[0119] (Where, X is a functional group containing a reactive group, R...) 6 and R 7 Each group can independently represent a hydrogen atom, an aliphatic hydrocarbon group, an aryl group, or a heterocyclic group with substituents.

[0120] Preferably, it is a compound described in the following general formula (3').

[0121] [Chemical Formula 3]

[0122]

[0123] (Where Y is an organic group, X' is a reactive group contained in X, and R...) 6 and R 7 (Same meaning as above)

[0124] Further preferred are compounds described in general formulas (3a) to (3d) as described below.

[0125] [Chemical Formula 4]

[0126]

[0127] When these compounds are incorporated into the adhesive composition, adhesion to the polarizer and the transparent protective film is sometimes improved, which is therefore preferred. From the viewpoint of improving the adhesion between the polarizer and the transparent protective film and the water resistance, in the curable water-dispersible composition, the content of the compound described in the above general formula (3) is preferably 0.001 to 50% by mass, more preferably 0.1 to 30% by mass, and most preferably 1 to 10% by mass.

[0128] In the above general formula (3), examples of aliphatic hydrocarbon groups include linear or branched alkyl groups with optional substituents having 1 to 20 carbon atoms, cyclic alkyl groups with optional substituents having 3 to 20 carbon atoms, and alkenyl groups with 2 to 20 carbon atoms. Examples of aryl groups include phenyl groups with optional substituents having 6 to 20 carbon atoms and naphthyl groups with optional substituents having 10 to 20 carbon atoms. Examples of heterocyclic groups include 5-membered or 6-membered ring groups containing at least one heteroatom and optionally substituents, which are optionally linked together to form a ring. In general formula (3), as R 6 and R 7 Preferably, it is a straight-chain or branched alkyl group with 1 to 3 carbon atoms, and most preferably a hydrogen atom.

[0129] The compound represented by general formula (3) has a functional group X containing a reactive group, which is a functional group that can react with the curing components that constitute the adhesive layer. Examples of reactive groups contained in X include: hydroxyl, amino, aldehyde, carboxyl, vinyl, (meth)acryloyl, styrene, (meth)acrylamide, vinyl ether, epoxy, oxetyl, α,β-unsaturated carbonyl, mercapto, halogen, etc. When the curable resin composition constituting the adhesive layer is ray-curable, the reactive group contained in X is preferably selected from at least one reactive group selected from vinyl, (meth)acryloyl, styrene, (meth)acrylamide, vinyl ether, epoxy, oxetyl, and mercapto. In particular, when the adhesive composition constituting the adhesive layer is free radical polymerizable, the reactive group contained in X is preferably selected from at least one reactive group selected from (meth)acryloyl, styrene, and (meth)acrylamide. When the compound represented by general formula (1) has a (meth)acrylamide group, it has high reactivity and a higher copolymerization rate with the ray-curable resin composition, which is more preferable. In addition, the (meth)acrylamide group has high polarity and excellent adhesion, which is also preferable from the perspective of efficiently obtaining the effects of the present invention. When the curable resin composition constituting the adhesive layer is cationic polymeric, the reactive group contained in X preferably has at least one functional group selected from hydroxyl, amino, aldehyde, carboxyl, vinyl ether, epoxy, oxetyl, and mercapto. In particular, when epoxy is present, the resulting curable resin layer has excellent adhesion to the adherend, and is therefore preferred. When vinyl ether is present, the curability of the curable resin composition is excellent, and is therefore preferred.

[0130] In this invention, the compound represented by general formula (3) can be a compound formed by direct bonding of reactive groups and boron atoms. However, as shown in the specific examples above, the compound represented by general formula (3) is preferably a compound formed by bonding reactive groups and boron atoms via organic groups, that is, preferably a compound represented by general formula (3'). When the compound represented by general formula (3) is, for example, a compound bonded to reactive groups via oxygen atoms bonded to boron atoms, there is a tendency for the adhesion and water resistance of the polarizing film to deteriorate. On the other hand, when the compound represented by general formula (3) does not have boron-oxygen bonds but has boron-carbon bonds by bonding boron atoms to organic groups, and contains reactive groups (in the case of general formula (3')), the adhesion and water resistance of the polarizing film is improved, and therefore preferred. The aforementioned organic groups specifically refer to organic groups with 1 to 20 carbon atoms that are optionally substituented. More specifically, examples include: linear or branched alkylene groups with 1 to 20 carbon atoms that are optionally substituented; cyclic alkylene groups with 3 to 20 carbon atoms that are optionally substituented; phenylene groups with 6 to 20 carbon atoms that are optionally substituented; and naphthylene groups with 10 to 20 carbon atoms that are optionally substituented.

[0131] As compounds represented by general formula (3), in addition to the compounds exemplified above, esters formed by hydroxyethyl acrylamide and boric acid, esters formed by hydroxymethyl acrylamide and boric acid, esters formed by hydroxyethyl acrylate and boric acid, and esters formed by hydroxybutyl acrylate and boric acid, etc., formed by (meth)acrylates and boric acid, can also be exemplified.

[0132] Cationic polymeric compounds used in cationic curable resin compositions can be classified into monofunctional cationic polymeric compounds having one cationic polymeric functional group within the molecule, and polyfunctional cationic polymeric compounds having two or more cationic polymeric functional groups within the molecule. Since monofunctional cationic polymeric compounds have lower liquid viscosity, the liquid viscosity can be reduced by including them in the cationic curable resin composition. Furthermore, monofunctional cationic polymeric compounds generally possess functional groups exhibiting various functions; by including them in the cationic curable resin composition, various functions can be exhibited in the cationic curable resin composition and / or the cured product of the cationic curable resin composition. Polyfunctional cationic polymeric compounds can cause three-dimensional crosslinking of the cured product of the cationic curable resin composition; therefore, it is preferable to include polyfunctional cationic polymeric compounds in the cationic curable resin composition. Regarding the ratio of monofunctional cationic polymeric compounds to polyfunctional cationic polymeric compounds, it is preferable to mix the polyfunctional cationic polymeric compounds in the range of 10 to 1000 parts by mass relative to 100 parts by mass of the monofunctional cationic polymeric compound. Examples of cationic polymeric functional groups include epoxy groups, oxetyl groups, and vinyl ether groups. Examples of compounds containing epoxy groups include aliphatic epoxy compounds, alicyclic epoxy compounds, and aromatic epoxy compounds. Due to their excellent curability and adhesive properties, alicyclic epoxy compounds are particularly preferred as the cationic polymeric adhesive composition of the present invention. Examples of alicyclic epoxy compounds include 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate, caprolactone-modified versions of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate, trimethylcaprolactone-modified versions, and valproic acid-modified versions. Specific examples include CELLOXIDE 2021, CELLOXIDE 2021A, CELLOXIDE 2021P, CELLOXIDE 2081, CELLOXIDE 2083, CELLOXIDE 2085 (all manufactured by Cello Chemicals Co., Ltd.), Cyracure UVR-6105, Cyracure UVR-6107, Cyracure 30, and R-6110 (all manufactured by Dow Chemical Japan Ltd.). Compounds containing oxocyclic butyl groups are preferred because they improve the curability of cationic polymeric curable adhesive compositions and reduce the liquid viscosity of the composition.Examples of compounds containing oxetane groups include 3-ethyl-3-hydroxymethyloxetane, 1,4-bis[(3-ethyl-3-oxetane)methoxymethyl]benzene, 3-ethyl-3-(phenoxymethyl)oxetane, di[(3-ethyl-3-oxetane)methyl] ether, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, and phenolic varnish oxetane. Commercially available examples include ARON OXETANE OXT-101, ARON OXETANE OXT-121, ARON OXETANE OXT-211, ARON OXETANE OXT-221, and ARON OXETANE OXT-212 (all manufactured by Toa Synthetic Co., Ltd.). Compounds containing vinyl ether groups are preferred because they improve the curability of cationic polymerizable adhesive compositions and reduce the liquid viscosity of the composition. Examples of compounds containing a vinyl ether group include 2-hydroxyethyl vinyl ether, diethylene glycol monovinyl ether, 4-hydroxybutyl vinyl ether, diethylene glycol monovinyl ether, triethylene glycol divinyl ether, cyclohexanediethanol divinyl ether, cyclohexanediethanol monovinyl ether, tricyclodecane vinyl ether, cyclohexyl vinyl ether, methoxyethyl vinyl ether, ethoxyethyl vinyl ether, and pentaerythritol-type tetravinyl ether.

[0133] The cationic polymerizable curable resin composition contains at least one compound selected from the above-described compounds having epoxy groups, oxetyl groups, and vinyl ether groups as a curing component. These are all substances that are cured by cationic polymerization, and therefore a photocationic polymerization initiator is incorporated. This photocationic polymerization initiator generates cationic species or Lewis acids upon irradiation with active energy rays such as visible light, ultraviolet light, X-rays, and electron beams, thereby initiating the polymerization reaction of epoxy groups and oxetyl groups. As a photocationic polymerization initiator, a photoacid generator described later can be appropriately used. Furthermore, when using a cationic polymerizable adhesive composition as a visible light curable material, a photocationic polymerization initiator with high sensitivity to light above 380 nm is particularly preferred. However, photocationic polymerization initiators are compounds that typically exhibit maximum absorption in the wavelength region around 300 nm or shorter than 300 nm. Therefore, by incorporating a photosensitizer that exhibits maximum absorption in a longer wavelength region, specifically longer than 380 nm, light at nearby wavelengths can be sensed, promoting the generation of cationic species or acids from the photocationic polymerization initiator. Examples of photosensitizers include anthracene compounds, pyrene compounds, carbonyl compounds, organosulfur compounds, persulfides, redox compounds, azo and diazo compounds, halogen compounds, and photoreducing pigments; two or more of these can also be used in combination. Anthracene compounds are particularly preferred due to their excellent photosensitizing effect; specific examples include Anthracure UVS-1331 and Anthracure UVS-1221 (manufactured by Kawasaki Chemical Co., Ltd.). The photosensitizer content is preferably 0.1% to 5% by mass, more preferably 0.5% to 3% by mass.

[0134] The polarizing film of the present invention can be manufactured, for example, by the following method for manufacturing polarizing films, which includes:

[0135] A polarizer manufacturing process involves processing a given location on one side of a polarizer with a processing liquid to form a non-polarizing portion with a recess on one side; a coating process involves applying a curable resin composition to the surface of the polarizer with the recess; a bonding process involves attaching a transparent protective film to the surface of the polarizer coated with the curable resin composition; and a bonding process involves bonding the polarizer and the transparent protective film together through an adhesive layer, wherein the adhesive layer is obtained by curing the curable resin composition by irradiating it with active energy rays from the polarizer surface side or the transparent protective film surface side. The polarizer manufacturing process may further include: a first step of temporarily attaching a surface protective film with through holes to one side of the polarizer to form a polarizing film laminate; a second step of processing a given location on one side of the polarizer with a processing liquid through the through holes in the surface protective film to form a non-polarizing portion with a recess on one side; and a third step of peeling off the surface protective film from the polarizer.

[0136] As a method for applying a curable resin composition to the concave surface of a polarizer, the appropriate method can be selected based on the viscosity of the composition and the target thickness. From the viewpoint of removing foreign matter from the polarizer surface and the coating properties, a post-measurement coating method is preferred. Specific examples of post-measurement coating methods include gravure roller coating, forward roller coating, air knife coating, and rod / stick coating. Among these, gravure roller coating is particularly preferred from the viewpoint of removing foreign matter from the transparent protective film surface and the coating properties.

[0137] Before the above-described coating process, an easy-to-adhere composition can be applied to the coating surface of the adhesive composition of the polarizer. As a method for applying the easy-to-adhere composition to the bonding surface of the polarizer, a post-application measurement method is preferred to achieve the same effect as the above-described coating process. When the easy-to-adhere composition contains a compound described in the above-described general formula (3), the adhesion between the polarizer and the transparent protective film is improved, which is therefore preferable.

[0138] In gravure roller coating, various patterns can be formed on the surface of the gravure roller, such as honeycomb patterns, trapezoidal patterns, grid patterns, conical patterns, or diagonal line patterns. To effectively prevent appearance defects in the final polarizing film, a honeycomb pattern is preferred for the surface of the gravure roller. In the case of a honeycomb pattern, to improve the surface finish of the coated surface after applying the easily bondable composition, the unit volume is preferably 1 to 5 cm². 3 / m 2 More preferably 2-3cm 3 / m 2Similarly, to improve the surface finish of the coated surface after applying the easily bondable composition, the number of lines per unit inch of roller is preferably 200 to 3000 lines per inch. Furthermore, the rotational speed of the gravure roller relative to the travel speed of the polarizing mirror is preferably 100 to 300%.

[0139] The polarizer is bonded to the transparent protective film by applying the curable resin composition as described above. The bonding of the polarizer to the transparent protective film can be performed using a roller laminator or the like.

[0140] After the polarizer is bonded to the transparent protective film, it is irradiated with active energy rays (electron beams, ultraviolet light, visible light, etc.) to cure the curable resin composition and form an adhesive layer. The irradiation direction of the active energy rays (electron beams, ultraviolet light, visible light, etc.) can be any suitable direction, but irradiation from the transparent protective film side is preferred. If irradiation is performed from the polarizer side, there is a concern that the polarizer may deteriorate due to the active energy rays (electron beams, ultraviolet light, visible light, etc.).

[0141] The irradiation conditions under electron beam irradiation are any conditions that can cure the aforementioned curable resin composition; any suitable conditions can be used. For example, the accelerating voltage for electron beam irradiation is preferably 5 kV to 300 kV, more preferably 10 kV to 250 kV. If the accelerating voltage is less than 5 kV, there is a concern that the electron beam may not reach the adhesive, resulting in insufficient curing. If the accelerating voltage is greater than 300 kV, there is a concern that the penetrating force through the sample may be too strong, causing damage to the transparent protective film and the polarizer. The irradiation dose is 5 to 100 kGy, more preferably 10 to 75 kGy. If the irradiation dose is less than 5 kGy, the adhesive will not cure sufficiently. If it is greater than 100 kGy, it will damage the transparent protective film and the polarizer, causing a decrease in mechanical strength, yellowing, and preventing the attainment of the desired optical properties.

[0142] Electron beam irradiation is typically carried out in an inert gas environment, but can also be performed in the atmosphere with a small amount of oxygen introduced, depending on the material of the transparent protective film. Depending on the material, by appropriately introducing oxygen, the surface of the transparent protective film initially irradiated by the electron beam can become oxygen-resistant, thereby preventing damage to the transparent protective film and allowing for efficient electron beam irradiation only on the adhesive.

[0143] In the above-described method for manufacturing polarizing films, the active energy rays used are preferably those containing visible light in the wavelength range of 380 nm to 450 nm, especially those containing the highest amount of visible light in the wavelength range of 380 nm to 450 nm. When using ultraviolet or visible light, if a transparent protective film (UV-opaque transparent protective film) is used, it will absorb light with wavelengths shorter than 380 nm. Therefore, light with wavelengths shorter than 380 nm will not reach the adhesive composition and will not contribute to its polymerization reaction. Furthermore, the light with wavelengths shorter than 380 nm absorbed by the transparent protective film is converted into heat, causing the transparent protective film itself to heat up, which can lead to defects such as curling / wrinkling of the polarizing film. Therefore, in this invention, when using ultraviolet or visible light, it is preferable to use a device that does not emit light with a wavelength shorter than 380 nm as the active energy ray generating device. More specifically, the ratio of cumulative illuminance in the wavelength range of 380–440 nm to cumulative illuminance in the wavelength range of 250–370 nm is preferably 100:0–100:50, more preferably 100:0–100:40. In the method for manufacturing the polarizing film of this invention, as the active energy ray, a gallium-encapsulated metal halide lamp or an LED light source emitting light in the wavelength range of 380–440 nm is preferred. Alternatively, a light source containing both ultraviolet and visible light, such as a low-pressure mercury lamp, medium-pressure mercury lamp, high-pressure mercury lamp, ultra-high-pressure mercury lamp, incandescent lamp, xenon lamp, halogen lamp, carbon arc lamp, metal halide lamp, fluorescent lamp, tungsten lamp, gallium lamp, excimer laser, or sunlight, can be used. Furthermore, ultraviolet light with wavelengths shorter than 380 nm can be blocked using a bandpass filter. To improve the adhesion of the adhesive layer between the polarizer and the transparent protective film and to prevent the polarizing film from curling, it is preferable to use a gallium-encapsulated metal halide lamp and to use active energy rays obtained by passing through a bandpass filter that can block light with a wavelength shorter than 380 nm, or active energy rays with a wavelength of 405 nm obtained by using an LED light source.

[0144] It is preferable to heat the adhesive composition before irradiating it with ultraviolet or visible light (pre-irradiation heating), in which case it is preferable to heat it to 40°C or higher, more preferably to 50°C or higher. Alternatively, it is also preferable to heat the active energy ray-cured adhesive composition after irradiating it with ultraviolet or visible light (post-irradiation heating), in which case it is preferable to heat it to 40°C or higher, more preferably to 50°C or higher.

[0145] In practical applications, the polarizing film of the present invention can be fabricated into an optical film laminated with other optical layers. There are no particular limitations on the optical layer; for example, one or more layers of reflective plates, semi-transparent plates, phase retardation plates (including half-wave plates, quarter-wave plates, etc.), viewing angle compensation films, and other optical layers sometimes used in the formation of image display devices can be used. Particularly preferred are reflective polarizing films or semi-transparent polarizing films formed by further laminating reflective plates or semi-transparent reflective plates onto the polarizing film of the present invention; elliptical polarizing films or circular polarizing films formed by further laminating phase retardation plates onto the polarizing film; wide-viewing-angle polarizing films formed by further laminating viewing angle compensation films onto the polarizing film; and polarizing films formed by further laminating brightness-enhancing films onto the polarizing film.

[0146] The optical film formed by stacking the aforementioned optical layers on a polarizing film can also be formed by sequentially stacking them one by one during the manufacturing process of an image display device, etc. However, pre-stacking the optical film has advantages such as superior quality stability and assembly operation, thereby improving the manufacturing process of the image display device, etc. Appropriate bonding methods such as adhesive layers can be used during the stacking process. When bonding the aforementioned polarizing film and other optical films, their optical axes can be configured at appropriate angles based on the target phase difference characteristics, etc.

[0147] An adhesive layer for bonding with other components such as liquid crystal cells can also be provided on the aforementioned polarizing film or an optical film having at least one layer of polarizing film. There are no particular limitations on the adhesive forming the adhesive layer; adhesives using polymers such as acrylic polymers, silicone polymers, polyesters, polyurethanes, polyamides, polyethers, fluorinated polymers, and rubber polymers as the base polymer can be appropriately selected. Acrylic adhesives, which exhibit excellent optical transparency and moderate wetting, cohesiveness, and adhesion properties, as well as excellent weather resistance and heat resistance, are particularly preferred.

[0148] The adhesive layer can be provided on one or both sides of the polarizing film or optical film in the form of a laminate of layers with different compositions or types. Furthermore, when provided on both sides, adhesive layers with different compositions, types, and thicknesses can be formed on the front and back surfaces of the polarizing film or optical film. The thickness of the adhesive layer can be appropriately determined according to the intended use, adhesion strength, etc., and is typically 1–100 μm, preferably 5–30 μm, and particularly preferably 10–20 μm.

[0149] The exposed surface of the adhesive layer is temporarily bonded to and covered by the diaphragm for the purpose of preventing contamination until it is put into actual use. This prevents contact with the adhesive layer under normal handling conditions. As the diaphragm, suitable diaphragms as previously specified can be used, in addition to the thickness requirements described above, by coating suitable thin materials such as plastic films, rubber sheets, paper, cloth, nonwoven fabrics, meshes, foam sheets, metal foils, and their laminates with appropriate release agents such as silicone, long-chain alkyl, fluorine, or molybdenum sulfide as needed.

[0150] [Image display device]

[0151] The polarizing film of the present invention can be preferably used in the formation of various devices such as image display devices. The formation of an image display device can be performed in a conventional manner. That is, an image display device is typically formed by appropriately assembling a liquid crystal cell with a polarizing film or optical film, and components such as an illumination system used as needed, and incorporating a driving circuit. In the present invention, there are no particular limitations except for the use of the polarizing film or optical film of the present invention, and conventional methods can be followed. Regarding the liquid crystal cell, any type of liquid crystal cell, such as TN type, STN type, or π type, can be used.

[0152] Suitable image display devices, such as image display devices with polarizing films or optical films disposed on one or both sides of a liquid crystal cell, and liquid crystal display devices using backlights or reflectors in their lighting systems, can be formed. In this case, the polarizing film or optical film of the present invention can be disposed on one or both sides of the liquid crystal cell. When polarizing films or optical films are disposed on both sides, they can be the same or different. Furthermore, during the formation of the image display device, one or more suitable components, such as diffuser plates, anti-glare layers, anti-reflective films, protective plates, prism arrays, lens array sheets, light diffuser plates, and backlights, can be disposed at appropriate locations. In addition, examples of image display devices of the present invention include organic EL (field-emitting diode) display devices, PDP (plasma display panel), and electronic paper, and it is particularly preferred to use them in organic EL devices that use polarizers with high transmittance. Furthermore, as an application of the image display device, it is preferably used in applications requiring durability in high-humidity and high-temperature environments, such as foldable display devices and automotive display devices.

[0153] The polarizing film of the present invention has a non-polarizing portion formed in the polarizing lens, and therefore can be particularly suitable for image display devices with sensor functions, in which case the non-polarizing portion of the polarizing film is positioned corresponding to the camera portion.

[0154] Example

[0155] The following describes embodiments of the present invention, but the implementation of the present invention is not limited to these.

[0156] <Polarization Film Manufacturing>

[0157] Examples 1-8 and Comparative Example 1

[0158] As the resin substrate, a strip-shaped, amorphous polyethylene terephthalate (IPA) copolymer film (100 μm thickness) with a water absorption rate of 0.75% and a Tg of 75°C was used. One side of the substrate was corona-treated, and an aqueous solution containing polyvinyl alcohol (degree of polymerization 4200, degree of saponification 99.2 mol%) and acetyl-modified PVA (degree of polymerization 1200, acetyl-modification rate 4.6%, degree of saponification ≥ 99.0 mol%, manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER Z200") in a 9:1 ratio was coated on the corona-treated surface at 25°C and dried to form a 13 μm thick PVA resin layer, thus creating a laminate.

[0159] The resulting laminate was subjected to unidirectional stretching (assisted stretching in a gas atmosphere) along the longitudinal direction (length direction) to 2.4 times its free end length in an oven at 120°C between rollers with different circumferential speeds. Next, the laminate was immersed in an insoluble bath (a boric acid aqueous solution prepared by adding 4 parts by mass to 100 parts by mass of water) at 30°C for 30 seconds (insoluble treatment). Then, it was immersed in a dyeing bath at 30°C, adjusting the iodine concentration and immersion time to achieve a given transmittance for the polarizer. In this embodiment, it was immersed in an iodine aqueous solution prepared by adding 0.2 parts by mass of iodine and 1.5 parts by mass of potassium iodide to 100 parts by mass of water for 60 seconds (dyeing treatment). Next, it was immersed in a crosslinking bath at 30°C (a boric acid aqueous solution prepared by adding 3 parts by mass of potassium iodide and 3 parts by mass of boric acid to 100 parts by mass of water) for 30 seconds (crosslinking treatment). Then, the laminate was immersed in a boric acid aqueous solution (prepared by adding 3 parts by mass of boric acid and 5 parts by mass of potassium iodide to 100 parts by mass of water) at a liquid temperature of 70°C, and simultaneously subjected to unidirectional stretching (stretching in aqueous solution) along the longitudinal direction (length direction) between rollers with different circumferential speeds to achieve a total stretch ratio of 5.5. Next, the laminate was immersed in a cleaning bath at a liquid temperature of 30°C (prepared by adding 4 parts by mass of potassium iodide to 100 parts by mass of water) (cleaning treatment).

[0160] Next, a free radical polymerizable curable resin composition is coated on the second transparent protective film, and the surface of the PVA resin layer of the above-obtained laminate is bonded to the second transparent protective film. The adhesive is cured by irradiating the second transparent protective film with ultraviolet light.

[0161] Then, the substrate was peeled off from the PVA resin layer to obtain a strip-shaped polarizing film (polarizer / second transparent protective film) with a width of approximately 1300 mm. It should be noted that the polarizer has a thickness of 5 μm and a monomer transmittance of 40.8%.

[0162] (Ultraviolet rays)

[0163] As an active energy ray, an ultraviolet (gallium-encased metal halide lamp) irradiation device was used: the Light HAMMER10 manufactured by FusionUV Systems, Inc., valve: V valve, peak illuminance: 1600 mW / cm². 2 Cumulative radiation dose 1000 mJ / cm 2 (Wavelength 380–440 nm). It should be noted that the ultraviolet irradiance was measured using the Sola-Check system manufactured by Solatell.

[0164] An adhesive (acrylic adhesive) was applied to one side of an ester resin film with a width of approximately 1300 mm and a thickness of 38 μm, resulting in a thickness of 5 μm. Using a sharp tool, through-holes with a diameter of 2.8 mm were formed on the ester resin film with adhesive at intervals of 250 mm along the length direction and at intervals of 400 mm along the width direction.

[0165] The ester resin film with adhesive was adhered to the polarizing lens side of the obtained polarizing film using a roll-to-roll method. Polarizing films with polarizing lenses having non-polarizing portions of varying thickness and hardness were manufactured by processing the polarizing films of Examples 1-8 and Comparative Example 1 under the processing conditions described in Table 2. It should be noted that, regarding the processing conditions described in Table 2, "NaOH treatment time" refers to the time (seconds) during which the polarizing film was immersed in a 1 mol / L (1N) sodium hydroxide aqueous solution, "HCl treatment time" refers to the time (seconds) during which the polarizing film was immersed in 1 mol / L (1N) hydrochloric acid, and "drying temperature" refers to the drying temperature (°C) after NaOH and HCl treatments.

[0166] The ester resin film was peeled off from the laminate obtained above. Next, regarding Examples 5 and 7-8, before bonding the peeled surface of the ester resin film of the laminate to the first transparent protective film, an easy-to-adhere component 1 (ACMO 70 wt%, pure water 27.8 wt%, VBPA 2 wt%, EXP4200 0.2 wt%) (coating thickness 1 μm) was applied to the peeled surface using a gravure roller coating method equipped with a gravure roller, and air-dried at 25°C for 1 minute (thickness after drying 0.7 μm). Next, for Examples 1-8, adhesive components 1-6 were applied to the bonding surface of the acrylic resin film (thickness 40 μm) serving as the first transparent protective film, and the adhesive was cured by irradiation with the same ultraviolet light as described above. The thickness of the cured adhesive layer is recorded in Table 2. The composition of adhesive components 1-6 is shown in Table 1. In Comparative Example 1, adhesive composition 7 (a PVA-based resin aqueous solution of 5% by weight resin concentration and 95% by weight water, manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER Z-200") was applied to the bonding surface of an acrylic resin film (40 μm thick) serving as the first transparent protective film, such that the thickness of the adhesive layer after heating reached 0.1 μm, and then bonded to the release surface of the ester resin film. The film was then heated in an oven at 80°C for 5 minutes. It should be noted that the viscosity of the adhesive composition before curing was 10 mPa·s.

[0167]

[0168] The constituent materials listed in Table 1 are as follows.

[0169] ACMO (acryloylmorpholine); trade name "ACMO", manufactured by KJ Chemical Co., Ltd.

[0170] 1,9-NDA (1,9-nonanediol diacrylate), trade name "LIGHT ACRYLATE 1, 9ND-A", manufactured by Kyoei Chemical Co., Ltd.

[0171] P2H-A (phenoxy diethylene glycol acrylate); trade name "LIGHT ACRYLATE P2H-A", manufactured by Kyoei Chemical Co., Ltd.

[0172] HEAA (Hydroxyethyl Acrylamide); trade name "HEAA", manufactured by Kojin Co., Ltd.

[0173] BYK UV3505 (UV-curing surface conditioner); trade name "BYK UV3505", manufactured by BYK Japan Co., Ltd.

[0174] Omn907 (2-methyl-1-[4-(methylthio)phenyl]-2-morpholino-1-propanone); trade name "Omnirad907", manufactured by IGMresins.

[0175] Omn819 (bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide); trade name "Omnirad 819", manufactured by IGMresins.

[0176] DETX (diethylthioxanthone); trade name "KAYACURE DETX-S", manufactured by Nippon Kayaku Co., Ltd.

[0177] UP-1190 (an acrylic oligomer synthesized by polymerizing (meth)acrylic acid monomers); trade name "ARUFONUP1190", manufactured by Toa Synthetic Co., Ltd.

[0178] VPBA (4-vinylphenylboronic acid); trade name "4-vinylphenylboronic acid", manufactured by Tokyo Chemical Industry Co., Ltd.

[0179] HPAA (hydroxypentanoic acid diacrylate); trade name "LIGHT ACRYLATE HPPA", manufactured by Kyoei Chemical Co., Ltd.

[0180] M5700 (2-Hydroxy-3-phenoxypropyl acrylate); trade name "ARONIX M5700", manufactured by Toa Synthetic Co., Ltd.

[0181] DEAA (Diethylacrylamide); trade name "DEAA", manufactured by KJ Chemical Co., Ltd.

[0182] FA1DDM (unsaturated fatty acid hydroxyalkyl ester modified ε-caprolactone (monomer component with hydroxyl groups)); trade name "PLACCEL FA1DDM", manufactured by Daicel Co., Ltd.

[0183] 9EGA (PEG400#Diacrylate); trade name "LIGHT ACRYLATE 9EG-A", manufactured by Kyoei Chemical Co., Ltd.

[0184] EXP4200 (leveling agent); trade name "Olfine EXP.4200", manufactured by Nissin Chemical Industry Co., Ltd.

[0185] A polarizing film with a first transparent protective film / polarizer was fabricated as described above. It should be noted that the first transparent protective film corresponds to... Figure 1 The transparent protective film 3 constituting the polarizing film 10 shown corresponds to the polarizing mirror. Figure 1 The polarizer 1 that constitutes the polarizing film 10 shown has an adhesive layer that bonds the first transparent protective film to the polarizer. Figure 1 The adhesive layer 2 constituting the polarizing film 10 is shown. It should be noted that a second transparent protective film is used in this embodiment, but a phase retardation film can also be used instead. The thickness and properties of the obtained polarizing film are shown in Table 2.

[0186]

[0187] In Table 2, the thickness d1 (μm) of the non-polarizing portion of the polarizer and the thickness d2 (μm) of the adhesive layer at the junction with the recess were measured using a scanning electron microscope (ZYGO, product name "New View 7300"). Additionally, the thickness d3 (μm) of the first transparent protective film was measured using a digital micrometer (Anritsu, product name "KC-351C").

[0188] In Table 2, the hardness H1 (GPa) of the non-polarized portion, the hardness H2 (GPa) of the portion of the adhesive layer in contact with the recess, the hardness H3 (GPa) of the transparent protective film, and the stress relaxation rate (%) of the portion of the adhesive layer in contact with the recess were measured using the following methods.

[0189] Using a nanoindenter (manufactured by Bruker Japan Co., Ltd., Triboindenter TI-950), a Bercovici-type indenter (manufactured by Bruker Japan Co., Ltd., indenter for Triboindenter TI-950 (model TI-0039; Bercovici-type diamond indenter, front opening angle 142.3°) is pressed into the center of the part of the polarizing film to be measured (for example, the center of the non-polarizing part when measuring the hardness H1 of the non-polarizing part, and the center of the transparent protective film in the thickness direction when measuring the hardness H3 of the transparent protective film) for 50 nm. The maximum load (Pmax) and the contact area between the indenter and the measured part (contact projection area) (A) are measured, and the hardness (GPa) is calculated based on the following formula.

[0190] (Hardness (GPa)) = (Pmax) / (A)

[0191] The load was measured 50 nm after the indenter was pressed into the polarizing film for 40 seconds, and the stress relaxation rate (%) was calculated based on the ratio to the initial load.

[0192] To confirm the effect of suppressing the expansion of bubbles present in the polarizing film, especially near the non-polarizing portion of the polarizing mirror formed in the polarizing film, the expansion rate of bubbles in the polarizing film was evaluated.

[0193] <Expansion rate of bubbles>

[0194] For the polarizing films of Examples 1-8 and Comparative Example 1, polarizing films without bubbles of a size unsuitable for use as products were pre-selected using an optical microscope. Then, an adhesive layer was applied to the transparent protective film side of the polarizing film to prepare a polarizing film with an adhesive layer. A CO2 laser (manufactured by COMNET Corporation, product name: Laser Pro-SPIRIT) was used, such as... Figure 2 As shown, a polarizing film with an adhesive layer and a non-polarizing portion 1A formed at the center was cut out (sample size 5cm × 5cm), and bonded to 0.5mm thick alkali-free glass to prepare a sample. The sample was placed in an environment of 85℃-85% humidity for 72 hours, and the expansion rate of bubbles before and after immersion was measured using an optical microscope (sample number 3). An expansion rate of less than 15% is considered practical for a polarizing film; the lower the expansion rate, the better the visual recognition of the polarizing film, even under high temperature and high humidity conditions. It should be noted that the CO2 laser irradiation conditions are as follows.

[0195] (irradiation conditions)

[0196] Wavelength: 10.6μm

[0197] Laser output power: 30W

[0198] Oscillation mode: Pulse oscillation

[0199] Laser diameter: 70μm

[0200] Laser irradiation surface: Protective film side

[0201] <Evaluation of the Curlability of Polarizing Films>

[0202] A sample was prepared by cutting the polarizing film at 100mm × 150mm with the long side of the film as the stretching direction. The sample was placed on a horizontal plane with the convex side facing down, and the distances from the horizontal plane to four points at the ends of the sample were measured. A polarizing film with an average distance of less than 20mm at the four points was considered to have sufficiently suppressed curling (◎), and a polarizing film with an average distance of 20mm to 30mm at the four points was considered to be at a practical level (○).

[0203] As can be seen from Table 2, compared with Comparative Example 1, Examples 1-8 all suppressed the expansion of bubbles present near the non-polarized portion of the polarizing mirror formed on the polarizing film, resulting in excellent visual recognition.

Claims

1. A polarizing film, wherein a transparent protective film is laminated on at least one side of a polarizing lens through an adhesive layer. The polarizing mirror has a non-polarizing portion with a concave portion formed on one side. The adhesive layer is formed from a cured layer of an active energy ray-curable resin composition. When the hardness of the non-polarized portion is set to H1 (GPa), the thickness of the thinnest portion is set to d1 (μm), the hardness of the portion of the adhesive layer that contacts the recess is set to H2 (GPa), and the thickness of the thickest portion is set to d2 (μm), H2×(d2 / d1)≥0.

044.

2. The polarizing film according to claim 1, wherein, When the stress relaxation rate of the portion of the adhesive layer that contacts the recess is set to O2, O2<70%。 3. The polarizing film according to claim 1, wherein, H1×d1>1.

3.

4. The polarizing film according to claim 1, wherein, When the hardness of the transparent protective film stacked on the concave side of the polarizing mirror is set to H3 (GPa) and the thickness is set to d3 (μm), H3×d3>4.

5. The polarizing film according to claim 1, wherein, The maximum depth dh of the recess is 0.1~2.0μm.

6. The polarizing film according to claim 1, wherein, The adhesive layer between the portion of the polarizer (excluding the non-polarizing part) and the transparent protective film has a thickness of less than 2 μm.

7. An image display device comprising a polarizing film according to any one of claims 1 to 6, wherein the non-polarizing portion of the polarizing film is disposed at a position corresponding to a sensor portion.

Citation Information

Patent Citations

  • Polarizer, polarizing plate and image display device

    JP2015215609A

  • Method of producing polarizer

    JP2015215610A

  • Input / output device and method for driving input / output device

    JP2015215611A

  • Method for producing long adhesive film

    JP2016027135A

  • Long adhesive film

    JP2016027136A